Global prevalence and contributing factors of transplant renal artery stenosis in renal transplant recipients: A systematic review and meta-analysis - Tamara, Fredo; Fajar, Jonny K.; Gersom, Camoya; Wicaksono, Ramadi S.; Tupamahu, Alvira R.; Huda, Fariz N.; Sari, Fitria R.; Dela, Jamaludin A.; Putri, Irawati E.; Sutrisno, Muhammad A.; Putra, Riyantono; Dwinata, Michael; Friatna, Yudha; Albaar, Thoha M.; Susanto, Agung; Dewi, Ratih TK.; Suseno, Aryo; Samsu, Nur (Narra J, 2024)
Transplant renal artery stenosis (TRAS) is a serious complication of renal transplantation, with its prevalence and associated factors remaining inconclusive. The aim of this study was to assess the global prevalence and risk factors associated with TRAS incidence in renal transplant recipients. We conducted a meta-analysis by collecting data on the prevalence and factors associated with TRAS from articles in Scopus, Embase, and PubMed. The prevalence of TRAS was determined using a single-arm meta-analysis. The factors associated with TRAS were determined using Mantel-Haenszel analysis or inverse variance analysis. Out of 28,599 articles from the searches, 31 of them were included in the analysis. The global prevalence of TRAS was 6% among renal transplant recipients. Diabetes mellitus, hypertension, longer duration of dialysis before transplant, deceased donor, acute rejection, delayed graft function, longer cold ischemic time, and prolonged peak systolic velocity were associated with an increased risk of TRAS. Age, gender, peripheral artery disease (PAD) comorbidity, causes of end-stage renal disease (ESRD), previous dialysis modality, and cytomegalovirus infection were not associated with TRAS incidence. In conclusion, the global prevalence of TRAS in renal transplant recipients is relatively high, and some of the contributing factors to the development of TRAS are preventable. These findings could serve as a guideline for informing the management of TRAS in the future.